Enhancing the sensitivity of portable biosensors based on self-powered ion concentration polarization and electrical kinetic trapping. (March 2020) - Fan, Yu-Jui; Huang, Ming-Zheng; Hsiao, Yu-Cheng; Huang, Yu-Wen; Deng, Chih-Zong; Yeh, Cheng; Husain, Rashaad A.; Lin, Zong-Hong
Abstract: Preconcentration of biomolecules for detection on microfluidic platforms based on electrical kinetic trapping (EKT) through ion concentration polarization (ICP) has been well developed in the past decade. Biomolecules can be entrapped due to the equilibrium of forces between electro-osmosis and ICP when applying a voltage to the system. However, the voltage required to trigger ICP phenomena in microfluidics is normally 30–80 V DC, which is a barrier to ICP-based nanofluidic preconcentrators becoming portable point-of-care devices. In this study, we developed a triboelectric nanogenerator (TENG)-driven nanofluidic preconcentrating device that is able to trigger ICP and subsequently cause the EKT of the biomolecules without using a conventional electrical power source. The EKT and electrical characteristics of the TENG-based nanofluidic preconcentrator were studied. Furthermore, the TENG-based nanofluidic preconcentrator was integrated with a smartphone-enabled bead immunoassay to become a portable and highly sensitive biosensor. The preconcentration and trapping processes were developed, and the bead-immunoassay on a smartphone with/without preconcentration was demonstrated to determine the preconcentration factors. Graphical abstract: Self-powered nanofluidic preconcentrator: Nanofluidic preconcentrator has been used for accumulating low-abundance biomolecules before detection. A triboelectric nanogenerator is used to trigger the preconcentration process. The self-powered nanofluidic preconcentrating device is also integrated with a bead-immunoassay and quantified using a smartphone, showing great potential as a sensitive portable biosensor. Image 1 Highlights: Self-powered ICP-based preconcentration through a TENG-driven smartphone-enabled bead immunoassay has been demonstrated. Preconcentration plug effects from both vertical contact-separation and rotary sliding mode TENG have been investigated. The preconcentrating plug generated in 1 min by hand-clapping of TENG enabled a preconcentration factor of 1000-fold.